Description Of The Rules For The Evaluation Of External Signs In Physiognomics And Their Printouts, As Well As Research In The Field Of Pathophysiognomics - Polvanov Rasulbek Baxtiyarovich; Faqirov Alijon Zohidovich (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
This article analyzes the rules and principles of assessment of external signs in physiognomy, the shape of the face, the appearance of its limbs, the identification of symptoms depending on the change, the description of the study.